X-ray excited luminescence of Ga- and In-doped ZnO microrods by annealing treatment. (October 2016) - Li, Qianli; Liu, Xiaolin; Gu, Mu; Huang, Shiming; Zhang, Juannan; Ni, Chen; Liu, Bo; Hu, Yahua; Wu, Qiang; Zhao, Shuning
Abstract: Ga- and In-doped ZnO microrods were prepared by low temperature hydrothermal process, and the effect of annealing temperature on morphology, crystallization, photoluminescence and X-ray excited luminescence were deeply researched. The results showed that both Ga- and In-doped ZnO microrods were possessed of a good crystalline quality and exhibited an intense visible emission band with a blue-shift under X-ray excitation. This blue-shift of the visible luminescence could be ascribed to the different contributions of the defect emissions, i.e. the increase in the oxygen vacancy ( V O ) emission and the decrease of the oxygen interstitial ( O i ) emission. Moreover, a strong ultraviolet luminescence was also obtained by further hydrogen annealing. It is expected that Ga- and In-doped microrods are promising candidates for development of fast and high-spatial-resolution X-ray imaging detectors. Highlights: A slightly etching appeared on the surface of Ga- and In-doped ZnO nanorods after annealing at 1000 °C. The doped ZnO nanorods exhibited a strong visible emission band with a blue-shift under X-ray excitation. An intense superfast ultraviolet emissions were observed after further hydrogen annealing.